2013
DOI: 10.1080/00049670.2013.771767
|View full text |Cite
|
Sign up to set email alerts
|

Website designers: how do they experience information literacy?

Abstract: This paper presents the findings from the first phase of a larger study into the information literacy of website designers. Using a phenomenographic approach, it maps the variation in experiencing the phenomenon of information literacy from the viewpoint of website designers. The current result reveals important insights into the lived experience of this group of professionals. Analysis of data has identified five different ways in which website designers experience information literacy: problemsolving, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…They experience information literacy as the ability to recognize, access, and use textual, physical and social sites of information specific to workplace context and work practices (Lloyd, 2009). Web designers experience information literacy as problem solving, using best practices and knowledge bases, building successful websites, and participating in learning communities (Sayyad Abdi et al, 2013). Based on the studies discussed above, the experience of using information varies considerably according to the context in which the workplace is embedded.…”
Section: Background and Research Hypotheses Information Literacy In Tmentioning
confidence: 99%
“…They experience information literacy as the ability to recognize, access, and use textual, physical and social sites of information specific to workplace context and work practices (Lloyd, 2009). Web designers experience information literacy as problem solving, using best practices and knowledge bases, building successful websites, and participating in learning communities (Sayyad Abdi et al, 2013). Based on the studies discussed above, the experience of using information varies considerably according to the context in which the workplace is embedded.…”
Section: Background and Research Hypotheses Information Literacy In Tmentioning
confidence: 99%
“…The idea of information experience design emerged from my interest in translating the theoretical understanding of IL into practice. The idea emerged from reflections on my doctoral study (Sayyad Abdi, 2014;Sayyad Abdi et al, 2016) which took a relational view of IL. From a relational perspective, a phenomenon is seen as the logically structured complex of the different ways of experiencing an object, for example information (Marton, 2014).…”
Section: Where This Idea Comes Frommentioning
confidence: 99%
“…Early WIL research is valuable because it identified IL as an important facet of the 21 st century workplace. Modern WIL research seeks to establish the contextual parameters of IL in workplace settings by mapping the lived experience of individuals employed in different sectors, organisations, roles, and locations [17], [20], [21], [22], [23], [24], [25], [26].…”
Section: Workplace Information Literacy (Wil)mentioning
confidence: 99%